Revisiting the Marketing of the Indonesian Batik and the Nigerian Adire - Anele, Kalu Kingsley; Cho, Young-Rae (International Journal of Culture and Art Studies, 2022)
This paper aims to fill the gap in the marketing of Batik and Adire. The methodology deployed is a comparative analysis of literature and legal instruments. The paper also uses data to comparatively analyze the impact of the marketing of Batik and Adire in the creative industries in Indonesia and Nigeria. The paper’s findings show that both fabrics share some commonalities in making them, and their designs have sociocultural meanings. They contribute to sustainable socio-economic and cultural development of both countries. Moreover, both fabrics have cultural, aesthetic, artistic, and religious values. They play significant roles in tourism, art-craft, the creative industry, and the way of life of Indonesians and Nigerians. Both fabrics require similar measures to enhance their marketing strategies given their marketing limitations. Conclusively, common measures can be used to enhance the marketing of both fabrics in terms of the use of technology. Hence, both countries should put appropriate legal regimes, regulatory frameworks, facilities, and infrastructure in place to achieve that. Also, the creation of textile cottage industries, the establishment of small and medium enterprises, and public-private partnerships are key in bolstering the marketing of Batik and Adire.